A lipid-based parallel processor for chemical signals - Cazimoglu, I (2021)
A key goal of drug delivery and bottom-up synthetic biology is to construct structures that interact with their environment. Biological cells and tissues can process several external chemical signals, often in parallel, without cross-talk. However, so far, cell- and tissue-like structures with only one signalling pathway have been generated. Here, using lipid-bounded aqueous compartments, we build a three-compartment processor with an architecture analogous to that of dual-core central processing units. Each compartment is optimised for a distinct task such as signal transmission, sensing, and enzymatic processing. Recombinantly generated pore-forming membrane protein alpha-hemolysin in the signal transmission compartment enables fast exchange of chemicals between the processing compartments and the external environment. The processor can receive two chemical signals from the environment, process them orthogonally, and produce an output for each signal. The output can be fluorescence or the production and release of a molecule into the external environment. We build the processor from the bottom up, in a modular fashion. In two compartment processors containing a signal transmission compartment and another compartment of varying contents, we demonstrate signal release, signal intake, enzymatic DNA cleavage and enzymatic hydrolysis. We then combine various compartments to build three-compartment processors able to process chemical signals in parallel.